A STUDY OF AN ORDER IN RAPID RESPONSE TO EMERGENCIES IN THE DANGEROUS GOODS TRANSPORTATION BY RAIL - Radkevych, A. V.; Yakovlev, S. O.; Shaptala, O. I.; Kramar, I. Ye. (Science and Transport Progress, 2008)
The paper is devoted to the problems of determination of rules and order of application, interaction of subdivisions of the State Special Service of Transport with subdivisions of the Ministry of Transport and Communications of Ukraine and the Ministry of Ukraine on Issues of Extraordinary Situations and in Affairs of Population Protection from the Aftermaths of Chernobyl Catastrophe during elimination of aftermaths of accidents with dangerous freights on the railway transport.